Complete bladder duplication presenting in adulthood: A case report on reconstructive technique and reflections on translational urology in refugees - Abramowitz, David; Claeys, Wietse; Jamaer, Caroline; Berquin, Camille; Hoebeke, Piet; Spinoit, Anne-Françoise (Frontiers in Urology, 2023)
Introduction and aim of study: The bladder-Exstrophy-Epispadias (BEEC) complex is a spectrum of congenital malformations with many variations. A never operated political refugee with BEEC was referred to our center for management upon arrival in Europe. Our aim is to report the technique and outcomes on a never operated on BEEC adult, highlighting the importance of transitional urologic care for congenital malformations in adult patients. Materials and Methods A 27-year old female patient was referred to our center for complete incontinence since birth by the General practitioner from the refugee center who suspected BEEC. Upon further investigation, an exstrophic bladder with blind ending ureteral orifices and a urethral meatus caudal to the exstrophic bladder plate were highlighted (see figure 1&2). A second non-exstrophic bladder with two orthotopic ureters was demonstrated, thereby a bladder duplication in the sagittal plane was diagnosed, presenting a wide-open bladder neck and a 7 cm pubic diastasis, causing the incontinence she was initially referred for. With the patient in a supine position, laparotomy incision was done with excision of the umbilical scar. The exstrophic bladder plate is dissected caudally. As it presents good detrusor quality, decision is taken to use it as a ventral inlay to augment the non-exstrophic bladder . A Mitchell-type bladder neck reconstruction is performed with a classical fascia sling wrapped around the bladder neck to increase the continence mechanism given the very wide pubic diastasis. Given the risk for hyper-continence, interposition of a continent Mitrofanoff-type vesicostomy is additionally realized. Genital reconstruction is achieved. Results Over 1 year post operatively, the patient is completely dry, can holp up to 250ml between catheterization she performs five times per day and once at night. No post-operative complications were observed. Conclusion The case of one adult patient with a rare urological condition like bladder exstrophy with duplication is presented, illustrating challenges political refugees referred to Europe implicates in terms of surgery regarding congenital malformations in adult patients. A multidisciplinary approach is highly important, demonstrating the importance of transitional care.